2022
DOI: 10.1080/13869795.2022.2051592
|View full text |Cite
|
Sign up to set email alerts
|

What’s special about ‘not feeling like oneself’? A deflationary account of self(-illness) ambiguity

Abstract: The article provides a conceptualization of self(-illness) ambiguity and investigates to what extent self(-illness) ambiguity is 'special'. First, we draw on empirical findings to argue that self-ambiguity is a ubiquitous phenomenon. We suggest that these findings are best explained by a multidimensional account, according to which selves consist of various dimensions that mutually affect each other. On such an account, any change to any particular self-aspect may change other self-aspects and thereby alter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Here, the challenge becomes to explain the nature of such evaluative construals in a way that imputes enough irrationality to recalcitrant emotion. To highlight this challenge, Helm (2001) draws an analogy between recalcitrant emotions and 13 The self-ascription of thoughts, beliefs, or emotions linked to the disorder raises interesting questions with respect to the "self-illness ambiguity" phenomenon (see Sadler 2007;Dings and de Bruin 2022). One might think that it matters for questions about irrationality whether a person ascribes a particular thought, emotion, etc.…”
Section: The Irrationality Of Recalcitrant Emotionsmentioning
confidence: 99%
“…Here, the challenge becomes to explain the nature of such evaluative construals in a way that imputes enough irrationality to recalcitrant emotion. To highlight this challenge, Helm (2001) draws an analogy between recalcitrant emotions and 13 The self-ascription of thoughts, beliefs, or emotions linked to the disorder raises interesting questions with respect to the "self-illness ambiguity" phenomenon (see Sadler 2007;Dings and de Bruin 2022). One might think that it matters for questions about irrationality whether a person ascribes a particular thought, emotion, etc.…”
Section: The Irrationality Of Recalcitrant Emotionsmentioning
confidence: 99%
“…The X is the ambiguating factor; the thing that makes it unclear whether it is themselves or X that is making them desire, feel or do Y. There are numerous potentially ambiguating factors, coming from all domains of everyday life (Dings and De Bruin 2022), but in the context of clinical decision-making for patients with psychiatric problems it is particularly self-illness and self-medication ambiguities that are relevant.…”
Section: Distinguishing Self-ambiguity From Ambivalencementioning
confidence: 99%
“… 3 Several studies have indicated the viability of the PTS as a basis for understanding mental disorders ( Dings and de Bruin, 2016 ; Fingelkurts and Fingelkurts, 2017 ; Baird, 2019 ; Fingelkurts et al, 2020 , 2021 ; Neustadter et al, 2021 ; Ciaunica et al, 2022 : Dings and de Bruin, 2022 ; Zawadzki, 2022 ; Giommi et al, 2023 ), or more broadly for self-understanding ( Newen, 2018 ; Lindahl and Britton, 2019 ; Motta, 2023 ). …”
mentioning
confidence: 99%